Studies on Time of Seed Collection, Sowing and Presowing Seed Treatments of Terminalia bellirica Roxb. And Terminalia chebula Retz. - Bhardwaj, S. D.; Chakraborty, A. K. (Indian Forester, 1994)
In two years study, the overall perfonnance of Terminalia bellirica and T. chebula seedlings in the nursery were found better, when seeds were collected in first fortnight of January and sowing was done at last week and third week of March respectively. Presowing seed treatment on germination and growth of seedlings of T. bellirica produced better result when the seeds were soaked in concentrated sulphuric acid (H2SO4) for 12 minutes. The germination and growth of seedlings of T. chebula were maximum when the seeds were soaked in cold water for 24 hours before 5 week stratification in cowdung.